Direct Observation of Off‐Stoichiometry‐Induced Phase Transformation of 2D CdSe Quantum Nanosheets. Issue 7 (13th January 2023) - Ma, Hyeonjong; Kim, Dongjun; Park, Soo Ik; Choi, Back Kyu; Park, Gisang; Baek, Hayeon; Lee, Hyocheol; Kim, Hyeongseoung; Yu, Jong‐Sung; Lee, Won Chul; Park, Jungwon; Yang, Jiwoong
Abstract: Crystal structures determine material properties, suggesting that crystal phase transformations have the potential for application in a variety of systems and devices. Phase transitions are more likely to occur in smaller crystals; however, in quantum‐sized semiconductor nanocrystals, the microscopic mechanisms by which phase transitions occur are not well understood. Herein, the phase transformation of 2D CdSe quantum nanosheets caused by off‐stoichiometry is revealed, and the progress of the transformation is directly observed by in situ transmission electron microscopy. The initial hexagonal wurtzite‐CdSe nanosheets with atomically uniform thickness are transformed into cubic zinc blende‐CdSe nanosheets. A combined experimental and theoretical study reveals that electron‐beam irradiation can change the stoichiometry of the nanosheets, thereby triggering phase transformation. The loss of Se atoms induces the reconstruction of surface atoms, driving the transformation from wurtzite‐CdSe(11 2 ¯ 2 0) to zinc blende‐CdSe(001) 2D nanocrystals. Furthermore, during the phase transformation, unconventional dynamic phenomena occur, including domain separation. This study contributes to the fundamental understanding of the phase transformations in 2D quantum‐sized semiconductor nanocrystals. Abstract : This study reveals the mechanism for phase transformation of 2D CdSe quantum nanosheets induced by off‐stoichiometry. The loss of Se atoms in 2D wurtzite‐CdSe nanocrystals destabilizes the initial structure and modifies the surface atomic configuration to resemble zinc blende structure, which ultimately leads to phase transformation. Additional non‐conventional dynamic phenomena, including domain separation, are observed during the transformation.